Crossed Cerebellar Atrophy of the Lateral Cerebellar Nucleus in an Endothelin-1-Induced, Rodent Model of Ischemic Stroke - Chan, Hugh H.; Cooperrider, Jessica L.; Park, Hyun-Joo; Wathen, Connor A.; Gale, John T.; Baker, Kenneth B.; Machado, Andre G. (Frontiers in Aging Neuroscience, 2017)
Crossed cerebellar diaschisis (CCD) is a functional deficit of the cerebellar hemisphere resulting from loss of afferent input consequent to a lesion of the contralateral cerebral hemisphere. It is manifested as a reduction of metabolism and blood flow and, depending on severity and duration, it can result in atrophy, a phenomenon known as crossed cerebellar atrophy (CCA). While CCA has been well-demonstrated in humans, it remains poorly characterized in animal models of stroke. In this study we evaluated the effects of cerebral cortical ischemia on contralateral cerebellar anatomy using an established rodent model of chronic stroke. The effects of cortical ischemia on the cerebellar hemispheres, vermis and deep nuclei were characterized. Intracortical microinjections of endothelin 1 (ET-1) were delivered to the motor cortex of Long Evans rats to induce ischemic stroke, with animals sacrificed six weeks later. Naive animals served as controls. Cerebral sections and cerebellar sections including the deep nuclei were prepared for analysis, with Nissl staining. Cortical ischemia was associated with significant thickness reduction of the molecular layer at the Crus 1 and parafloccular lobule (PFL), but not in 4Cb, as compared to the ipsilesional cerebellar hemisphere. A significant reduction in volume and cell density of the lateral cerebellar nucleus (LCN), the rodent correlate of the dentate nucleus, was also noted. The results highlight the relevance of corticopontocerebellar projections for cerebellar metabolism and function, including its direct projections to the LCN.